2003
DOI: 10.1097/01.asn.0000070621.06264.86
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Allograft Function among Long-Term Kidney Transplant Recipients

Abstract: Abstract. Long-term kidney allograft survival continues to remain an elusive goal. Kidney transplant recipients are believed to be at high risk for loss of allograft function, and new, potentially non-nephrotoxic immunosuppressive medications are advocated to improve long-term allograft survival. To evaluate the efficacy of such therapeutic interventions, information regarding the change in GFR among kidney transplant recipients with long-term allograft survival is needed. We studied 40,963 transplant recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 30 publications
10
70
1
1
Order By: Relevance
“…This is in contrast to the decline of 1 to 3 ml/min per 1.73 m 2 /yr typically CLINICAL RESEARCH www.jasn.org observed with standard-dosage calcineurin inhibitors (CNIs) 9,10 and is consistent with the renal benefit seen with belatacept in the original study at 1 year. 7 It should be noted that in our study, the GFR at the beginning of the LTE was similar in the belatacept and CsA groups, despite a difference in favor of belatacept at the end of the original study.…”
Section: Discussionsupporting
confidence: 65%
“…This is in contrast to the decline of 1 to 3 ml/min per 1.73 m 2 /yr typically CLINICAL RESEARCH www.jasn.org observed with standard-dosage calcineurin inhibitors (CNIs) 9,10 and is consistent with the renal benefit seen with belatacept in the original study at 1 year. 7 It should be noted that in our study, the GFR at the beginning of the LTE was similar in the belatacept and CsA groups, despite a difference in favor of belatacept at the end of the original study.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, it was proposed that all grafts loose function at a slow but steady rate. It was suggested that the strategies for improvement baseline graft function, defined as GFR at post-transplant month 6, might be more important for graft outcome than those for a slowly declining GFR (9). As graft function at the end of the early post-transplant period depends on the quality of the transplanted kidney and early post-transplant events (15,16), we decided to analyze the transplantation outcome of living related donor grafts which avoided AR and DGF.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies kidney or graft function was most commonly estimated by creatinine clearance, as calculated by the Cockcroft-Gault formula, and the influence of donor factors was examined on graft function at multiple timepoints (3,7,8). Recently, several studies have evaluated the change of creatinine clearance in the post-transplant period and the influence of different factors on this continuous parameter (3,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Whether 1, 5, or 10 years after transplantation, the GFR based on serum creatinine places the majority of patients into the stage 3T CKD (41). As seen in Figure 3, kidney function is reasonably stable over time with a slight trend toward a decrease over years as indicated by the slight shift to the left (42). Overall kidney function decreases, which translates into a Ϫ0.33 Ϯ 0.87 drop during the first 2 years and a Ϫ2.68 Ϯ 0.44 drop after that or approximately an overall Ϫ1.66 Ϯ 0.51 drop each year.…”
Section: Monitoringmentioning
confidence: 91%